Juegos de la edad tardía by Luis Landero and Nietzschean perspectives - Popovic Karic, Pol (Revista de Letras, 2019)
This text analyzes the relation between Nietzschean paradigms and Juegos de la edad tardía by Luis Landero. The Dionysian impulse is combined with the will to power, will to risk and will to freedom in order to permit the protagonist to live in fantasies and real life. On one hand, Gregorio constructs an imaginary world; and on the other, he tries to dominate characters like Gil, professor´s assistant and his wife. The theoretical framework for this essay comes from the key publications of the German philosopher Friedrich Wilhelm Nietzsche: The Will to Power, Thus Spoke Zarathustra, Beyond Good and Evil, Human, All Too Human, among others.